Tierra del Fuego Reference Standard Earthquake Catalogue - Sabbione, Nora Cristina (2007)
Tierra del Fuego represents a tectonically very complex region and is a key area in the investigation of the geodynamic interaction among the South American, Antarctic and Scotia plates. The Island is crossed by a transforming margin characterized by a left lateral movement from the Scotia Ridge in the east to the Chilean Basin in the west. The Magallanes Fagnano system divides Tierra del Fuego in two continental blocks. The main fault, with E-W orientation, is parallel to the Fagnano lake mayor axis. This fault system constitutes the mayor segment of the SouthAmerican-Scotia border. The methods of quantitative seismology (seismometry) appear to be a particularly suitable approach both to increase the knowledge of its tectonic evolution and of the main structural characteristics if a suitable seismological database is available. Since the 1990s a local seismometric network in Tierra del Fuego, including permanent broadband and short period stations, provide the seismological information required to afford these kinds of studies. It would also allow proper monitoring of Tierra del Fuego seismicity for civil protection purposes considering the high risk of heavy damages in the towns of Ushuaia and Rio Grande in the eventuality of a major earthquake such as the 1949 one. It is known that the most fundamental information for a hazard assessment is the record of past earthquakes. Among the important concerns are the completeness of the catalogues and whether sufficient studies have been conducted to estimate the earthquake sizes and locations in order to assess the implications of a modern recurrence. Seismicity has been studied and records have been processed by Seisan Software, from Bergen University (Norway); a significant level of low to medium magnitude earthquakes with epicentre in Tierra del Fuego continental region and oceanic surrounding areas was found. More than 300 events has been identified during the period 1999-2006, some of them were felt by inhabitants of the island. The average magnitude was 2.0 and the greatest magnitude for that period in Isla Grande was the Mb = 3.7 earthquake with epicentre near Tolhuin City. In this work we present an earthquake catalogue from the region using data provided by bulletins of some nearer stations; data from National, Regional or International Centres like INPRES, CERESIS, ISC, USGS; relocated events from a work done in La Plata University; journalist information of macro seismic data and the study of seismicity mentioned. Also we present a macro seismic questionnaire written and some interviews to local inhabitants that are useful to collect information about the big earthquakes of the region, such as the 1949 one. Finally, the criteria used for this catalogue are those recommended by the GSHAP (Global Seismic Hazard Assessment Program) Steering Committee in order to develop the more complete Tierra del Fuego earthquake catalogue to serve as reference standard.